Studies of the Helconinae (Braconidae: Hymenoptera) of Cox's Bazar and Chittagong in Bangladesh (Chittagong University Journal of Biological Sciences, 2013)
Two genera of Helconinae (Hymenoptera: Braconidae) have been described and illustrated from the districts of Coxs Bazar and Chittagong in Bangladesh and a key for the genera is given. The genera are: Helcon Nees and Eubazus Nees. The genera Helcon and Eubazus are new records to the fauna of Bangladesh. DOI: http://dx.doi.org/10.3329/cujbs.v5i1.13368 The Chittagong Univ. J. B. Sci.,Vol. 5(1 &2):37-44, 2010